The Designing of Disk Type Peanut Shell Cracker - Tamrin, Tamrin (Jurnal Teknologi Pertanian, 2010)
The peanut shell cracker of cylinder type has been developed with the capacity of >150 kg/hour.  Meanwhile the peanut shell cracker of the medium scale has not been designed. This research was aimed to design the peanut shell cracker in medium scale.  The shelling mechanism of peanut shell cracker was based on the disk type rice peeler.  The peanut shell cracker peels the skin of peanut fruit by a pressure and friction.  The top of disk did not move and beneath of disk turned, and the feeder in hopper was placed at the top of disk.  The performance test of peanut shell cracker was based on clearance between two disks (5, 10, and 15 mm) and three level of rotation of beneath of disk were 90, 120 and 150 rpm.  The results showed that the shelling of peanut shell was optimum at 5 mm of clearance, and 90 rpm of rotation of beneath of disk.  The shelling efficiency was 93.06%.Key word: peanut shell cracker, peanut, disk type, medium scale